HERPES ASSOCIATED ERYTHEMA MULTIFORME (HAEM) : CASE REPORTS - Fitria Mailiza (Odonto : Dental Journal, 2022)
Background: Erythema Multiforme (EM) is a mucocutaneous inflammatory reaction with clinical manifestations ranging from mild to severe which are self-limiting but can also be life-threatening. EM is considered an immunological disease in the form of a hypersensitivity reaction caused by an immune response to certain antigens such as herpes simplex virus known as Herpes Associated Erythema Multiforme (HAEM) or certain types of drugs known as Drug Induced Erythema Multiforme (DIEM). Hematinic factors greatly affect the length of the healing process in cases and can also worsen anemia because there is a tendency for bleeding on the lips. Case and Management: This case report discusses the case of EM in a 41-year-old woman who came to the practice with complaints of canker sores and scabs on her lips, disappearing and bleeding easily. The patient's condition is accompanied by chronic anemia with results of Hb, MCV, MCH, MCHC (below the reference value). Anti HSV IgG examination was 44.2 (reactive) so that HAEM was diagnosed with chronic anemia. Pharmacological management was given paracetamol, acyclovir, folic acid, Fe, and vitamin B12. Lip lesions are given a blended ointment. Provided education and instructions to patients to maintain nutritional intake, adequate rest and regular use of drugs. Conclusion: The healing condition can be faster by paying attention to the chronic anemia condition experienced by the patient.